Two new species of Daemonorops from Sulawesi - Rustiami, Himmah (REINWARDTIA, 2009)
Daemonorops mogeana Rustiami and Daemonorops takanensis Rustiami are described and illustrated for the first time based on specimens collected from Central Sulawesi and South Sulawesi respectively. An identification key of Daemonorops in Sulawesi is constructed in order to differentiate between those two species and other species of Daemonorops in Sulawesi.